2014
DOI: 10.1186/s40693-014-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Host plant specificity of the moth species Glena mielkei (Lepidoptera, Geometridae) in northern Chile

Abstract: Background: Host plant specificity refers to the preference of insects for particular plant species that allow them to complete their life cycle. Moth species of the Geometridae family depend closely on the vegetation composition to complete their life cycles. In northern Chile, the Geometridae species Glena mielkei is the only species described of the genus Glena. So far, this species has only been associated to a single host plan species of the Asteraceae family, Trixis cacalioides. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Trixis cacalioides is native to the coastal valleys of the Atacama Desert of northern Chile (Zöllner 1976, Katinas 1996, where it is also used by some native hostspecialist Lepidoptera (Vargas 2011, Méndez-Abarca et al 2014. Furthermore, the near threatened status has been recently proposed for this shrub in the study site (Gatica-Castro et al 2015).…”
mentioning
confidence: 99%
“…Trixis cacalioides is native to the coastal valleys of the Atacama Desert of northern Chile (Zöllner 1976, Katinas 1996, where it is also used by some native hostspecialist Lepidoptera (Vargas 2011, Méndez-Abarca et al 2014. Furthermore, the near threatened status has been recently proposed for this shrub in the study site (Gatica-Castro et al 2015).…”
mentioning
confidence: 99%
“…Host plant ranges from narrow to wide have been described for species inhabiting the west tropical Andes (Brehm, 2002(Brehm, , 2003Bodner et al, 2010), while larvae of more than 20 species have been found associated with a single host plant in the Brazilian cerrado (Marconato et al, 2008). Although host plants are highly relevant in the life cycles of geometrid moths, the records remain incomplete for the species of the transverse valleys of the Atacama Desert (Méndez-Abarca et al, 2014), hindering the understanding of other interactions. Recent fieldwork enabled the discovery of the first host plant of the little-known geometrid moth Cosmophyga cortesi Vargas, 2008, expanding its previously documented altitudinal range, and DNA barcodes confirmed the use of its larvae as prey by a potter wasp.…”
mentioning
confidence: 99%
“…According to Auad et al (2009), Embrapa Gado De Leite (2009), and Oliveira et al (2010), the aphid species S. flava and R. maidis are found in the highest frequency on P. purpureum, and the other 2 species are found on Brachiaria decumbens Stapf, which indicates the suitability of these forage species for those species of aphids; however, the reasons these forages are suitable for a particular aphid species have yet to be determined. The specificity of a host plant is measured by the ability to stimulate an insect to locate that host and to act as a suitable food substrate (Méndez-Abarca et al 2014). Studies that examine these relationships should be incorporated at the earliest stages of pest control programs because the effectiveness of integrated pest management is based initially on those insects that have a close relationship with their host plants.…”
mentioning
confidence: 99%